High Intensity Resistance Training Methods with and without Protein Supplementation to Fight Cardiometabolic Risk in Middle-Aged Males: A Randomized Controlled Trial - Kemmler, Wolfgang; Wittke, Andreas; Bebenek, Michael; Froehlich, Michael; von Stengel, Simon (BioMed Research International, 2016)
Time-effective protocols may potentially increase people's compliance with exercise. The purpose of this paper was to compare the relative effects of 16 weeks of high intensity (resistance) training (HIT) with and without protein supplementation (HIT&P) and HVHIT (high volume/high intensity training) versus a nontraining control group on cardiometabolic risk factors. One hundred and twenty untrained males 30-50 years old were randomly assigned to 3 subgroups: (a) a HIT group; (b) a HIT&P group, and (c) a waiting-control group (phase I) that crossed over to (d) high volume/high intensity training (HVHIT) during the second study phase. HIT was defined as "single set to failure protocol" while HVHIT consistently applied two sets. Protein supplementation provided an overall intake of 1.5 g/kg/body mass. Primary study endpoint was the metabolic syndrome Z-Score (MetS-Z-Score). MetS-Z-Score significantly improved in all exercise groups (p ≤ 0.001) with no significant difference between HIT, HIT&P, and HVHIT (p ≥ 0.829). However, all the exercise groups differed significantly from the CG (p < 0.001) which deteriorated significantly (p = 0.039). In conclusion, all exercise protocols were similarly effective in improving cardiometabolic risk factors. Thus, HIT may be the best choice for people with low time budgets looking to improve their cardiometabolic health.
EVALuna2:33291